Long‐distance non‐line‐of‐sight ultraviolet communication channel analysis: experimentation and modelling. Issue 5 (1st October 2015) - Liao, Linchao; Drost, Robert J.; Li, Zening; Lang, Tian; Sadler, Brian M.; Chen, Gang
Abstract : In this study, the long‐distance non‐line‐of‐sight (NLOS) ultraviolet (UV) communication channel is characterised using experimental data and theoretical modelling. Experimental measurements of path loss and pulse broadening effects at distances of up to 4 km are reported and analysed, and comparisons between the field test data and a Monte Carlo multiple‐scattering channel model provides strong evidence for the validity of the theoretical modelling approach. In addition, measurements probing the effects of turbulence are also considered, but in this case, the authors find limited experimental support for existing turbulence models, an important result suggesting the need for refined turbulence modelling. Finally, implications for NLOS UV communication performance at long ranges are examined. Overall, the experimental and numerical results serve to advance the study of NLOS UV channel modelling, an essential component of communication system design.